PENGUKURAN PROBABILITAS KEBANGKRUTAN DAN VALUASI OBLIGASI KORPORASI DENGAN METODE CREDITRISK+ - Yudia Yustine; Abdul Hoyyi; Di Asih I Maruddani (Jurnal Gaussian, 2012)
In capital market investment particularly the bonds, an investor must consider the credit risk and valuation of bonds. Credit risk refers to the risk due to unexpected changes in the credit quality of a counterparty or issuer. Valuation is amount that investor will receive on future. CreditRisk+ is from Reduced-Form Model which is used to calculate the probability of default and valuation of bonds. This method assumes that default occurs without warning and is therefore unpredictable. Default arrival is described by a Poisson process. Default intensity can expected by rate of corporate. An empirical example use a data set of bond from PT Berlian Laju Tanker, Tbk between 2007 and 2012. Probability of default from Berlian Laju Tanker III Bond is 0,6321206 and its valuation is Rp 153.481.545.500,00.